Patterns of library use by U.P. Rural High School students - Gapud, Lourdes P.; Hidalgo, Namnama P.; Picache, Ursula G. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1985)
The main objective of this study was to determine the nature and extent of library use by the University of the Philippines Rural High School (UPRHS) students by year level, sex, proximity of residence, and academic performance. The study looked into the reasons for library use or non-use, the subjects for which the library was most used, the library materials consulted or read, the materials wanted but not available, and the materials recommended to be added to the UPRHS Library collection. Use of the UPRHS Library as well as of the Main Library of the University of the Philippines at Los Baños (UPLB Library) was investigated.
Data were gathered through a questionnaire administered by subject teachers in SY 1983-1984. Five hundred fifty students responded, representing 95 percent of the student population. Statistical treatment of data consisted of frequencies, ranking of frequencies, percentages, z-test, t-test and chi-square.
About 88 percent of the 1983-1984 UPRHS students were users of both the UPRHS and UPLB Libraries. Only 15 or 2.7 percent of the respondents did not go to both libraries. Library use was found not to differ significantly by year level and proximity of residence to the UPRHS Library. However, library use differed significantly with sex and academic performance. The major reasons for the students' use of the two libraries were to read for their studies and for entertainment or relaxation. The high school library was more often used for leisure reading, for study purposes and to borrow books. The UPLB Library supplemented the UPRHS Library as a source of more books, research abstracts and periodicals.
There was a significant difference in library use among the school subjects. Students used the library much more for Literature, Science, Social Studies and Pilipino. The encyclopedias were the most popular references. For the non-fiction books, students tended to limit their use to textbooks and reserve books. The three English newspapers and the few periodicals in the UPRHS Library were avidly read for relaxation.
The UPRHS Library's fiction collection was not very much used by the students. Of the 487 UPRHS Library users, 143 claimed to have borrowed library fiction books. They listed a total of 115 titles which were only 10 percent of the total fiction collection. Of these titles, 35 were required readings for Literature and Pilipino, and 80 were of the students' choice.
The students' responses reveal that they expect the library to provide most of the books needed for class work as well as enough periodicals for informational and recreational reading. The most frequent reasons given by nonusers of the UPRHS Library were: a) I just study from my notes at home, b) I have all the books I needed at home, c) I spend my free time to relax with friends, and d) The books I need are not in the library.
It may be concluded that the UPRHS and UPLB Libraries are performing a vital service in providing for the educational needs of the students. However, there is a need to replenish the UPRHS Library with more relevant, up-to-date and interesting books for young adults in order to enhance the effectiveness of library service and to fully meet the developmental and recreational needs of the students.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Library use studies--Philippines--Los Baño; Rural High School. Librar; University of the Philippines Los Bañ